2017
DOI: 10.1590/s0104-59702017000300009
|View full text |Cite
|
Sign up to set email alerts
|

Pangênese, genes, epigênese

Abstract: Pangênese, genes, epigênese Pangenesis, genes, epigenesisRecebido para publicação em agosto de 2015. Aprovado para publicação em maio de 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
1
0
2
Order By: Relevance
“…Galton observed that the children of economically successful people accompanied this socioeconomic condition with similar performances. He concluded, therefore, that if the poor remained poor, this was due to genetic inheritance, without taking into account the material circumstances of production and reproduction in a class society (Arcanjo & Silva, 2017;Gioppo, 1996). Eugenic principles and guidelines, at the end of the 19th century, ended up structuring, politically and ideologically, the way in which European and North American societies perceived social relations.…”
Section: The Emergency Of Eugenics and The American National Efficien...mentioning
confidence: 99%
“…Galton observed that the children of economically successful people accompanied this socioeconomic condition with similar performances. He concluded, therefore, that if the poor remained poor, this was due to genetic inheritance, without taking into account the material circumstances of production and reproduction in a class society (Arcanjo & Silva, 2017;Gioppo, 1996). Eugenic principles and guidelines, at the end of the 19th century, ended up structuring, politically and ideologically, the way in which European and North American societies perceived social relations.…”
Section: The Emergency Of Eugenics and The American National Efficien...mentioning
confidence: 99%
“…Galton observou que os filhos de pessoas bem-sucedidas economicamente acompanhavam essa condição socioeconômica com performances semelhantes. Concluiu, assim, que, se os pobres continuavam pobres, isso se devia à herança genética, sem levar em consideração as circunstâncias materiais de produção e reprodução em uma sociedade de classes (Arcanjo & Silva, 2017;Gioppo, 1996).…”
Section: O Surgimento Da Eugenia E a Eficiência Nacional Norte-americ...unclassified
“…Menos conhecida do que sua teoria evolutiva, Darwin publicou, em 1868 (três anos depois da publicação dos trabalhos de Mendel com ervilhas de cheiro), sua teoria da pangênese, para explicar a herança, baseada em noções como a herança dos caracteres adquiridos (DARWIN, 1868). Seus pressupostos teóricos, radicalmente diferentes daqueles de Mendel, permitiram que ambos tivessem conclusões inteiramente diferentes a respeito de um mesmo fenômeno (MAYR, 1982, p. 23;BIZZO;EL-HANI, 2009;SILVA, 2017).…”
Section: História Da Ciência Epistemologia E Dialéticaunclassified